Audiowizualne adaptacje "Króla Edypa" Sofoklesa - próba analizy socjologicznej = Audiovisual adaptations of "Oedipus the King" by Sophocles - a sociological analysis - Marczak, Mariola (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author of the article claims that film adaptations of literary works indicate not only the directors`personal interpretations of the literary sources but also reflect, in their social and political aspects,the place and time in which the adaptation has been prepared. The assumption is verified by ananalysis of three adaptations of the classical tragedy "Oedipus the King" by Sophocles: P.P. Pasolini`s filmand two television plays - one directed by Laco Adamik (1992) and the other by Gustaw Holoubek(2005).
Keywords: Sofokles (ok. 496 p.n.e.-406 p.n.e.); "Król Edyp"; adaptacja filmowa; adaptacja teatralna